1870 Haw. Sess. Laws 26, An Act to License the Carrying of Fowling Pieces and Other Fire-arms, chap. 20, §§ 1 to 3 - (:unkn) unknown (My University, 1870)
Required a license from the Minister of the Interior to use or carry for sporting purposes any gun, carbine, rifle, pistol, or other fire-arms. Licenses were priced at five dollars. Violators fined fifty dollars for every offense. Failure to pay the fine led to imprisonment at hard labour.
Keywords: REGISTRATION